When customer feedback sparks innovation: Self-efficacy as a psychological pathway in the tourism industry - Yao, Kai; Sangthong, Thaunjai; Khunthong, Ubonwan; Chen, Wei (Edelweiss Applied Science and Technology, 2025)
This study investigates how customer feedback stimulates employee innovative behavior in the tourism sector, with self-efficacy serving as a mediator and interpersonal sensitivity and work autonomy acting as moderators. Drawing on social cognitive theory and self-determination theory, a mixed-methods design was employed, combining PLS-SEM analysis with qualitative interviews. The results demonstrate that customer feedback exerts a significant positive effect on both self-efficacy and innovative behavior, confirming its central role in fostering employee innovation. Self-efficacy was identified as a strong mediator, while interpersonal sensitivity enhanced the translation of customer feedback into self-efficacy. Additionally, work autonomy strengthened the impact of self-efficacy on innovative behavior. Qualitative insights further illustrated how employees reinterpret customer input and generate creative solutions when empowered with autonomy and interpersonal attunement. Importantly, the empirical study was conducted in Xi'an, one of China's most dynamic tourism destinations, where the vibrant tourism market underscores the practical relevance of feedback-driven innovation. The findings contribute to the literature on the micro-foundations of innovation in tourism by linking external market signals with individual-level psychological mechanisms. They also offer practical implications for enhancing competitiveness through feedback systems, employee empowerment, and organizational support.